2023
DOI: 10.3389/fcvm.2023.1113827
|View full text |Cite
|
Sign up to set email alerts
|

The role of monocytes in thrombotic diseases: a review

Abstract: Cardiovascular and cerebrovascular diseases are the number one killer threatening people's life and health, among which cardiovascular thrombotic events are the most common. As the cause of particularly serious cardiovascular events, thrombosis can trigger fatal crises such as acute coronary syndrome (myocardial infarction and unstable angina), cerebral infarction and so on. Circulating monocytes are an important part of innate immunity. Their main physiological functions are phagocytosis, removal of injured a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 278 publications
0
9
0
Order By: Relevance
“…Multivariate regression analysis showed that patients with a high NLR (4.44) had a 2-fold higher risk of AT than those with an NLR < 4. 44 suggested that this association depended on the type of artery. This study indicated that a high NLR is related to a large cerebral artery with atherosclerosis, but it is not related to a small cerebral vessel.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Multivariate regression analysis showed that patients with a high NLR (4.44) had a 2-fold higher risk of AT than those with an NLR < 4. 44 suggested that this association depended on the type of artery. This study indicated that a high NLR is related to a large cerebral artery with atherosclerosis, but it is not related to a small cerebral vessel.…”
Section: Discussionmentioning
confidence: 99%
“…The role of monocytes in the pathogenesis of thrombosis is recognized; however, few studies have focused on the differences between AT subgroups. 44 Inflammation and NETs have been associated with thrombosis (VTE and AT). Studies were carried out to examine whether a high NLR may be a predictor of thrombosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monocytes/macrophages also participate in removing apoptotic cells and tissue debris, contributing to the resolution of inflammation. Due to the diverse functions that monocytes or macrophages perform during the development of inflammation and regulation of the coagulation cascade and tissue regeneration, dysregulation of their functions may affect coagulation disorders and thrombotic diseases such as Deep Vein Thrombosis (DVT) [ 74 , 89 , 90 ] and Pulmonary Embolism (PE) [ 90 , 91 ], Arterial Thrombosis [ 92 , 93 ], Disseminated Intravascular Coagulation (DIC) [ 94 ], Antiphospholipid Syndrome (APS) [ 95 , 96 ], or Thrombotic Microangiopathies [ 97 , 98 ], highlighting the importance of understanding their interaction with the coagulation system ( Table 2 ).…”
Section: Blood Coagulation Process and The Role Of Immune System Cellsmentioning
confidence: 99%
“…In doing so, monocytes and macrophages release TF, a key initiator of the coagulation cascade, leading to local activation of the clotting system and thrombus formation. Additionally, macrophages secrete various cytokines and growth factors that modulate endothelial function and contribute to the prothrombotic milieu [ 92 ].…”
Section: The Role Of the Coagulation System In Selected Disorders Of ...mentioning
confidence: 99%